Hypothetical Learning Trajectory Design of Sinus Rules Based on PBL with Ethnomathematics of Minangkabau Culture - Okta Vutri Nupus; Armiati Armiati; I Made Arnawa (Universitas Maritim Raja Ali Haji, 2022)
Based on the preliminary research, the tenth-grade students lacked ability in mathematical problem solving of sine rule. One of the factors that influenced this problem was the teacher's learning model, which was still mechanistic. The teacher did not relate between learning and environment or local culture. Based on this, this study aims to develop HLT on the topic of a valid ethnomathematical PBL-based sine rule. The development model used is the Plomp model and the Gravemeijer and Cobb model, which consists of the initial investigation stage, product development stage, and assessment stage. In this article, the discussion is focused on the HLT development stage. The data analysis technique used is descriptive statistics and descriptive techniques. Data collection instruments used: validation sheets, observation sheets, interview sheets, questionnaires, and field notes. This study resulted in the HLT of the sine rule based on PBL nuances of Minangkabau Culture, which met the validity criteria of 0.771 and the characteristics of validity in terms of content and constructs.